Psychometric Properties of Chinese Version of the Barriers to Error Disclosure Assessment (C-BEDA) Tool - Huang RR; Xie YS; Chen GR; Liu ZQ (Risk Management and Healthcare Policy)
Rong-Rong Huang,1 Yu-Sheng Xie,2 Gui-Ru Chen,3 Zhao-Qing Liu2 1Department of Burns and Plastic Surgery, The Affiliated Hospital of Guizhou Medical University, Guiyang, Guizhou, People’s Republic of China; 2School of Nursing, Guizhou Medical University, Guiyang, Guizhou, People’s Republic of China; 3Department of Infectious Diseases, The People’s Hospital of Aba Tibetan and Qiang Autonomous Prefecture, Aba, Sichuan, People’s Republic of ChinaCorrespondence: Gui-Ru Chen, Department of Infectious Diseases, The People’s Hospital of Aba Tibetan and Qiang Autonomous Prefecture, No. 176 Majiang Road, Maerkang, Aba Tibetan and Qiang Autonomous Prefecture, Sichuan, 624000, People’s Republic of China, Email 2017283030185@whu.edu.cnAim: The Barriers to Error Disclosure Assessment (BEDA) tool is used to measure barriers to the disclosure of medical errors by healthcare professionals. This study aimed to evaluate the psychometric properties of the Chinese version of the BEDA (C-BEDA).Background: The culture of disclosure and transparency in response to medical errors has been recommended in recent years. However, there are no relevant assessment tools for measuring barriers to disclosing medical errors in China.Methods: The C-BEDA tool underwent translation, back translation, cross-cultural adaptation in a pilot study. It was tested with 1254 healthcare professionals in Guizhou and Sichuan Provinces, China. The content validity index (CVI) was used to evaluate the content validity of the C-BEDA, and exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to evaluate its structural validity. The Cronbach’s α coefficient and test-retest reliability were evaluated to determine its reliability.Results: Three factors were extracted by EFA that explained 65.892% of the total variance of the C-BEDA tool. CFA showed a good fit for a three-factor structure with acceptable values: goodness-of-fit index=0.939; adjusted goodness-of-fit index=0.911; incremental fit index=0.967; comparative fit index=0.967; partial least squares path modeling for confirmatory factor analysis=0.735; and root mean square error of approximation=0.058. The item-level content validity index ranged from 0.86 to 1.00, and the average scale-level content validity index was 0.98. The Cronbach’s α coefficient (0.909) and test-retest reliability (0.86) were acceptable.Conclusion: The C-BEDA toolis a valid and reliable tool for assessing the extent of barriers to error disclosure among Chinese healthcare professionals.Keywords: patient safety, medical error, disclosure, risk management